PENGARUH JOB DESCRIPTION, JOB SPECIFICATION DAN HUMAN RELATION TERHADAP KINERJA KARYAWAN DEPARTEMEN PRODUKSI PT. AICE ICE CREAM JATIM INDUSTRY: EFFECT OF JOB DESCRIPTION, JOB SPECIFICATION AND HUMAN RELATION ON PERFORMANCE OF PRODUCTION DEPARTMENT EMPLOYEES PT. AICE ICE CREAM JATIM INDUSTRY - Dewi Andriani; Nur Raficha Dwi Setyohadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This research has a purpose to find out effect of Job Description, Job Specification and Human Relations on Employee Performance in the production department of PT. Aice Ice Cream Jatim Industry. Quantitative approach methods are carried out in this research. Sampling in this study was performed by non-probability sampling method with purposive sampling technique with respondents of 100 employees of the production department. The data analysis method for this study is multiple regression using the Statistical Program for Social Science (SPSS) for windows type 22.This is confirmed by the results of the investigation conducted that job description has a partial impact on employee performance, the job specification variable has a partial impact on employee performance and the human relationshas a partial impact on employee performance. Job description, job specification and human relations have a simultaneous effect on employee performance. Penelitian ini memiliki tujuan untuk mengetahui pengaruh Job Description, Job Specification dan Human Relation terhadap Kinerja Karyawan departemen produksi PT. Aice Ice Cream Jatim Industry.Metode pendekatan kuantitatif digunakan pada penelitian ini. Pengambilan sampel penelitian menggunakan teknik non-probability sampling yang dipilih pada penelitian ini ialah purposive sampling dengan responden sebanyak 100 karyawan departemen produksi. Teknik analisis data pada penelitian ini yakni regresi linier berganda dengan menggunakan Statistical Program for Social Science (SPSS) for windows type 22.Hal ini diperkuat dengan hasil yang menyatakan job description mempunyai dampak secara parsial terhadap kinerja karyawan, job specification memiliki pengaruh secara parsial terhadap kinerja karyawan dan human relation mempunyai dampak parsial terhadap kinerja karyawan. Job description, job specification dan human relation memiliki dampak secara simultan terhadap kinerja karyawan.